ANALISIS PENGARUH VARIABEL SOSIAL EKONOMI MASYARAKAT URBAN TERHADAP KEMANDIRIAN EKONOMI DITINJAU DARI ASPEK KEUANGAN, ENERGI, DAN PANGAN DI KECAMATAN SINGOSARI KABUPATEN MALANG - - Supartono; Khusnul Ashar; Mochamad Affandi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
This study aims to assess the contribution of local economic independence for theurban community village of Candi Renggo, Singosari District in the short term fromthe aspects of finance, energy and food; and analyze whether independence was simultaneously able to survive in the long run. The analysis showed that the economicand social resource for the urban community is quite adequate so that resources can besynergy between mutually exclusive and weaknesses. For the people in selected vil-lages have the ability to develop and demonstrate a significant contribution, althoughthe level is still low. The results of this study partially and simultaneously to thecombined respondents (agricultural and non agricultural sector) contribution provedadequate, but not yet able to explain in detail the contribution was sufficient forrespondents who work in agriculture and non agricultural sector alones.Keywords: local economic independence, urban society